Avaliação térmica do concreto nas primeiras idades - Duarte, Francisco Kléber Dantas (Universidade Federal Rural do Semi-Árido, 2018)
The analysis of temperature in the concrete core is a necessary resource to avoid pathological manifestations due to the heat of hydration. This work sought to analyze the temperature configuration in the concrete core in the initial dates, so that it is analyzed by numerical methods in the distribution of heat in the concrete mass. The factors influencing the temperature are the heat of hydration, the effects of heat, conduction, radiation and convection, as well as the initial and contour conditions of the concrete. For large concretes the main cause of concern is the thermal gradient, that is, a difference between the maximum and minimum means of the concrete is subject. For the possibility of a sufficient energy generation to be generated as a curve, a box with insulation was made, as well as a digital thermometer with thermocouple aid, fixed in the center of the box at a medium height, to coincide with the core of the concrete. The formation of this work was given as satisfactory for the needs, generating curves for a point of analysis and generated graphs with other literatures.
Keywords: Calor de hidratação; Temperatura; Manifestações patológicas; ENGENHARIAS::ENGENHARIA CIVIL